Comparison of carcass and lingual examination for the diagnosis of porcine cysticercosis in Nepal - Joshi, DD; Pandey, KR; Dorny, P; Bista, PR; Vercruysse, J (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> With the increase in pig production and consumption by smallholder, there have been problems with zoonotic parasitic diseases especially porcine cysticercosis in Nepal. Materials and Methods: This study was conducted among 320 pigs from four different slaughter slabs of Chitwan and Kathmandu valley during June to November 2006. The objectives of this study were to determine prevalence by lingual examination, carcass examination and to identify predilection sites of T. solium cysticercosis in pigs as well as to compare the lingual examination, carcass examination. Result: The prevalence rate of cysticercosis for lingual and carcass examination was 0.63%, 0.94% respectively. The incidence of cysticercosis was not significantly different (P>0.05) between the Chitwan and Kathmandu valley and lingual (P>0.05) and carcass examination (P>0.05). Similarly the incidence of the disease was not significantly (P>0.05) different among the slaughter slabs by lingual (P>0.05) and carcass examination (P>0.05). The common predilection sites of the cysts were skeletal muscle, diaphragm, heart, oesophagus and tongue. The sensitivity, specificity, positive and negative predictive values of Lingual examination, taking carcass examination, as gold standard was 50, 100, 100, 98.99 and 100, 82.65 respectively. Conclusion: Among the animal factor under study breed was found significantly (P < 0.05) associated with incidence of cysticercosis while the age and sex were not significant. Keywords: Lingual, porcine cysticercosis, carcass, neuroparasitic Journal of Institute of Medicine, www.jiom.com.np April, 2008; 30:1 11-17 The full text of this paper is available from the Journal of Institute of Medicine website